The Influence of Learning Styles on Senior High School Students’ Learning Outcomes and Its Supporting Factors - Adilla Lilik Dewi Kirana; Mudhar Mudhar (Indonesian Journal of Guidance and Counseling Studies, 2026)
Background: Student learning outcomes serve as a primary indicator of instructional effectiveness. However, variations in academic achievement are often influenced by individual characteristics, particularly learning styles. Understanding how visual, auditory, and kinesthetic learning preferences relate to academic performance is essential for developing more responsive instructional approaches. Objective: This study aimed to examine the relationship between visual, auditory, and kinesthetic learning styles and senior high school students’ learning outcomes. Method: A quantitative correlational design was employed involving 40 students. Data were collected through a Likert-scale learning style questionnaire and students’ report card scores. The data were analysed using Pearson product-moment correlation to determine the strength and significance of the relationships between variables. Result: The findings revealed significant positive correlations between learning styles and learning outcomes. The visual learning style showed a correlation coefficient of r = 0.421 (p = 0.008), the auditory learning style r = 0.356 (p = 0.024), and the kinesthetic learning style r = 0.389 (p = 0.014). These results indicate that students who effectively utilise their dominant learning styles tend to achieve higher academic performance. Conclusion: Learning styles are an essential internal factor influencing students’ academic achievement, though their impact interacts with other factors, such as physiological and psychological conditions, family support, school and community environments, and time management. Contribution: This study provides empirical evidence to support educators and schools in designing adaptive, multimodal, and student-centred instructional strategies to improve student learning outcomes.